Effect of pressure on superconductivity in the indium-doped topological crystalline insulator SnTe. (22nd May 2015) - Maurya, V K; Jha, R; Shruti,; Awana, V P S; Patnaik, S
Abstract: We report on the impact of hydrostatic pressure on the superconductivity of optimally (indium)-doped SnTe which is established to be derived from a topological crystalline insulating phase. Single crystals of Sn1− x In x Te were synthesized by a modified Bridgman method that exhibited maximum superconducting T c of 4.4 K for x = 0.5. Hydrostatic pressure up to 2.5 GPa was applied on the crystals of Sn0.5 In0.5 Te, and electrical resistivity as a function of temperature and pressure was measured. We observed a decrease in the onset superconducting transition temperature from 4.4 K to 2.8 K on increasing pressure from ambient to 2.5 GPa. The normal state resistivity also decreased abruptly by an order of magnitude at 0.5 GPa but for higher pressures, it decreased marginally. From onset, offset and zero resistivity values, d T c /d P of ∼ −0.6 K GPa −1 was confirmed. The low temperature normal state resistivity followed T 2 dependence suggesting Fermi liquid behaviour both for ambient and high pressure data. This increase in metallic characteristics accompanied by normal state Fermi liquid behaviour is in accordance with a 'dome structure' for T c variation with varying carrier concentration.